TRANSCULTURAL REPRESENTATION IN INDONESIAN EFL TEXTBOOKS: A CASE STUDY - Jimmy Sapoetra; Setiono Sugiharto; Luciana (University of Kuningan, 2026)
This study investigated the comprehensive depiction of culture within the framework of Global Englishes, offering a fresh outlook in English as a Foreign Language (EFL) education. This perspective transitioned from admitting the supremacy of the English language to acknowledging the existence of International English and English as a global language. This development has profoundly revolutionized the domain of English as a Foreign Language (EFL) education. This study aimed to examine the cultural material found in English as a Foreign Language (EFL) textbook, with a specific focus on how it is altered and influenced by the concept of transcultural flows. The predominant aim of research on cultural content has been to quantitatively delineate the proportion of said content. The investigations also explored the cultural categorization based on a wide range of cultural characteristics. They failed to analyse culture at the level of microcultures or the transfer of culture between various contexts. The study additionally examined the transcultural flows that occur across national and cultural boundaries, utilizing Pennycook's theory (2007) as a basis. The analysis uncovered dynamic interplays between the indigenous Indonesian culture and transcultural influences, notably focused on the act of borrowing and remaking in the English as a Foreign Language (EFL) textbook. The study highlighted the simultaneous presence and interplay of these borrowings and the indigenous Indonesian culture, offering pupils a chance to cultivate a comprehension of culture within a worldwide context. Moreover, this study revealed that the cultural depictions and their integration into Indonesian settings offer English education that beyond mere proficiency in the English language. The cultural representations and their position as borrowings offer opportunities for the advancement of English as a constituent of global Englishes.